Manhaj Shaykh Nawawi Al-Banteni dalam mensyarahkan hadis-hadis kitab nasa’ih al-‘ibad - Kirin, Arwansyah; Ismail, Faisal Husen; Abu Hassan, Muhammad Ikram (USIM Press, 2022)
Shaykh Nawawi al-Banteni is an Islamic scholar who produces various famous works in the Malay archipelago, especially in Indonesia. Among his famous works is the book Nasa'ih al-‘Ibad is one of the interprets or reviews from the book alMunabbahat ‘Ala al-‘Isti’dad Li Yaum al-Ma’ad by Ibn Hajar al-Asqalani. This book became a reference in some Indonesian Boarding Schools. In addition, it is also used as a study material in certain mosques. However, in-depth study of the method of hadith interpretation in the book is rarely observed by users of the book. Therefore, it is important to explain the method of hadith interpretation found in this book so that its status can be known as well as to measure the extent of its knowledge in the hadith. This study aims to explore the method of hadith interpretation conducted by Shaykh Nawawi al-Bantani in the book Nasa'ih al-‘Ibad. The purpose of this study is to determine and analyze the method of hadith interpretation used by Shaykh Nawawi al-Banteni and reveal the extent of his knowledge and status as a scholar of hadis through the book Nasa’ih al-‘Ibad. The methodology of this study is qualitative through library methods and content analysis design of Nasa’ih al-‘Ibad book. This study found that in general the method used by Shaykh Nawawi al-Banteni in interpreting hadith is by using the method of Ijmali. In its application, he uses textual interpretation techniques through the method of interpreting hadith according to the original material or text of hadith, and intertextual through the method of explaining the differences of material in hadith interprete, reciting hadith with hadith, reciting hadith with the words of scholars, reciting hadith with Arabic poetry. This study found that Shaykh Nawawi al-Banteni had good ability and knowledge in hadith. Apart from that, it can also provide an understanding to the community about the method of hadith interprete performed by Shaykh Nawawi al-Banteni in his book Nasa’ih al-‘Ibad.